The effect of Adding Ginger (zingiber officinale ) powder and folic acid on some blood traits in ration of Kids black local Goat - Hussain Al- Musodi, Mohaned Fadhl (Journal of Kerbala for Agricultural Sciences, 2018)
This study conduced in private farm in Karbala from 20/1/2016-15/7/2016 , the aim of this study is investiget the effect of zingiber officinale powder and folic acid added to Ration of local Iraqi Goat kids as afood addition on some blood triaits,18 Kids in 1-2 years old randomly divided to three group (6 each) Kids of first group (control ) free of any addition concentrated diet in percentage 2% of body weight with grazed on farm pasture , the 2nd group (T1) feeded on the same ration with adding 8 mg.kg concentration daite of folic acid as food addivites , the 3rd group (T2) feeded on same ration with 30 gr.kg concentration diat as afood addivites ,red blood cell ,white blood cells . heamoglobine,total blood protein , albumin and globuline are measured monthly,the results showed asignificant increase (P< 0.05) , in RBCs ,WBCs and Hb in T1 and T2 group compared with control group, total blood protein and globuline are asignificant increase (P< 0.05) in T2 group compared with control group , while bold albumin is no significant differ between all groups . .